The Effect of Synthetic Fertilizer Urea, TSP and ZA on Total Biomass and Chlorophyl Content of Dunaliella sp. - Junda, Muhammad; Adhyani, Andi Nurul; Muis, Abd; Kurnia, Nani; Rachmawaty, Rachmawaty (Bionature, 2024)
This research is an experimental research which aims to determine the effect of synthetic fertilizers urea, TSP and ZA on the amount of biomass and chlorophyll content of Dunaliella sp. on a laboratory scale. The research design used was a completely randomized design (CRD) consisting of 5 treatments with 3 replications each to obtain 15 treatment combinations. The research method consisted of several stages, namely preparation of tools and materials consisting of making culture media, making walne medium and making treatment medium, sterilizing tools and medium, preparing Dunaliella sp inoculum. on Walne medium with a static system, as well as optimizing the growth of Dunaliella sp.. The parameters observed in this study were phytoplankton biomass (dry weight), total chlorophyll content, salinity, pH, temperature, and light intensity. Based on the research results, the highest average biomass was found in the P3 treatment, namely the Walne medium treatment with the addition of 105 ppm urea, 80 ppm TSP, and 80 ppm ZA which produced an average of 5.23 g/L. Furthermore, the highest average results for measuring chlorophyll content were found in treatment P4 with walne medium treatment which added 115 ppm urea, 75 ppm TSP and 75 ppm ZA which produced an average of 1.81 µg/mL. So it can be concluded that the synthetic fertilizers urea, TSP and ZA have an effect on the amount of biomass and chlorophyll content on the growth of Dunaliella sp.